Production of NP Fertilizers Based on Local Raw Materials - Nazirova Rakhnamokhon Mukhtarovna; Mirsalimova Saodat Rakhmatjanovna; Makhmudov Asror (Research Parks Publishing LLC, 2021)
Phosphorites S.K are the main phosphate raw materials for the factories of Uzbekistan producing phosphorus-containing fertilizers. The article presents the kinetics of decomposition of phosphorites S.K. sulfuric and extraction phosphoric acids. According to the data obtained, most of the phosphorite (52-65%) decomposes within 10 minutes, and then the process of opening the phosphate is sharply measured. With an equal total rate of acids, an increase in the proportion of sulfuric acid contributes to a deeper decomposition of phosphate. For 3 hours of interaction, an increase in the amount of sulfuric acid contributes to an increase in the degree of opening of the fossil raw material from 83.9 to 90.1%, at a process temperature of 80 ° C at 90 ° C from 89.8 to 93%.